A Cross Sectional Study of Gender Differences in Internet Preferences and Usage Pattern among Medical Students in Sub Urban Region - Rajasekhar, P.; Veena, C. N.; Kumar, Srujan (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Back Ground: Internet began with the development of electronic computers in the 1950s.Internet usage has been rapidly increased in our daily life, and is directly affecting people’s ideas and behavior. With the development of the Internet, both male and female users to certain extent are unquestionably dependent on it as a medium of sharing ideas, building communication network as well as for searching information. Because of difference in opinion by the researchers regarding the internet usage among gender the present study is an attempt to quantify the gender difference in internet usage. Materials and Methods: A cross sectional study was carried on 120 first year MBBS students at tertiary care center. Data was collected with the help of a questionnaire. Results: The present study observed gender differences in awareness and pattern of internet use among first MBBS students which is relatively less compared to the previous studies. Conclusion: The Internet has become an inseparable part of today's educational system. The academics of an individual increasingly depends on the Internet for educational purposes. Absence of gender gap in internet usage is probably due to both genders having better exposure to the technology through their educational experience.